Analysis of bacterial diversity in healing and non-healing wounds among Malaysian subjects by phenotypic identification and 16S rDNA sequencing - Wong, S.; Manikam, R.; Muniandy, S. (2013)
Wound healing is a complex sequence of events consisting of regeneration and repair. It has been proposed that bacteria present in wounds play a major role in delayed wound healing. The main objectives of this study are to identify the bacterial species present in wounds and to evaluate and compare the results obtained using conventional biochemical analysis and 16S rDNA sequencing. Wound swabs from 15 healing and 15 non-healing wounds were collected from the wound clinic in University Malaya Medical Centre, Malaysia. The wound microbiotas obtained by bacterial culture methods followed by biochemical tests and 16S rDNA sequencing were compared. Culture analysis and 16S rDNA sequencing both revealed that the most prevalent bacteria in wounds are Staphylococcus spp. and Pseudomons spp. The prevalence of Staphylococcus aureus was significantly higher in non-healing wounds than healing wounds (p=0.003). API (R) biochemical tests successfully identified all 54 isolates at species level. However, by 16S rDNA sequencing only 19 (35.2) isolates were identified at species level and 35 (64.8) were identified at the genus or family level. 16S rDNA sequencing however provided a better view on the phylogenetic relationships of bacterial species present in wounds.